Desenvolvimento de um método para o processo de irradiação de hemocomponentes em acelerador linear - LARA, Vitor Carvalho (2017)
Transfusion of concentrated Red Blood Cell (CH) in humans can lead to Transfusion Associated Graft-versus-Host Disease (TA-GVHD), a rare and severe late transfusional reaction (RT) in immunosuppressed patients. This RT is an inflammatory response produced by T lymphocytes present in CH and other transfused cellular components. Irradiation of these blood components prior to transfusion is indicated to avoid TA-GVHD. The irradiator for blood products is rare in Brazil due to high cost, therefore, the ionizing radiation through a linear accelerator is the most widely used method. However, the irradiation procedure using linear accelerator is not standardized in the country and there is no container of suitable shape and size to accommodate such bags of blood components during the irradiation process. For this purpose a polycarbonate container was developed with appropriate measures for the packaging of the blood bags and standardized the blood irradiation process in the Radiotherapy Department of the Hospital de Clínicas of the Universidade Federal do Triângulo Mineiro (UFTM). This standardization was the result of several studies on the interaction of radiation with the container material and blood bags. The analyzes were made possible by the use of specific software in radiotherapy planning and by absolute measurements through precision dosimeters at various points within the container